The South African Dental Association (SADA) Celebrates World Oral Health Day 2023 by promoting Health Education and Awareness - Makhubele, KC (South African Dental Journal, 2023)
World Oral Health Day (WOHD) is a global initiative that takes place annually on 20th March to raise awareness about the significance of oral health and promote good oral hygiene practices. In South Africa, WOHD was celebrated with various activities and events organized and or coordinated by the South African Dental Association (SADA), aimed at promoting oral health education and awareness among the public.